Attitudes Of University Youth Towards External Marriage in the Shadow of The War on Syria ((A Field Study Conducted on Students in the Sociology Department)) (Damascus University Journal of arts and humanities sciences, 2021)
The study aims to identify the attitudes of the students of the Department of Sociology towards External marriage (marriage between different nationalities) in the period of the war on Syria, and the relationship between their attitudes and a number of variables related to them (gender, school year (first - fourth),age group, marital status, employment).An appropriate methodology was adopted for the purpose of this research, namely, the descriptive analytical method, and the method of social survey by sample, as away to observe the social reality.The questionnaire was also used as atool to collect general data about the sample of the  subjects. Likert scale likewise was utilized to measure the students' attitudes towards the studied subject.The original research community consists of the first and fourth year students (males and females) in the Department of Sociology,  for the academic year 2017-2018. The number of the students is (1486), including (1045) first year and (441) fourth year. The size of the sample was taken intentionally (142), 74 students from the first year, and 68 students from the fourth year. Based on the statistical analysis of the data carried out through the statistical program (SPSS) using measures: percentages, mean, standard deviation, statistical significance, a number of results were found indicating that the attitudes of university youth towards mixed marriage, Arab or marrying persons of foreign nationality who were neutral. The results also showed that there is no relationship between university youth attitudes towards External marriages (Arab and foreign) and a number of variables related to them: gender, basic environment, school year, and work. While it was found that there was a relationship between their attitudes and other variables represented by age group and their social status. The results also showed that the large percentage of sample units considered that marriage on a rational basis is one of the most important factors to achieve marital compatibility.
Keywords: Attitudes; University Youth; External Marriage; the War on Syria